# arrow_back Calculate the determinant $$\left|\begin{array}{rrrr} -2 & 1 & -1 & 1 \\ 3 & 2 & 0 & -4 \\ -1 & 1 & 2 & -1 \\ 1 & -1 & 3 & -2 \end{array}\right|$$

191 views
Calculate the determinant $$\left|\begin{array}{rrrr} -2 & 1 & -1 & 1 \\ 3 & 2 & 0 & -4 \\ -1 & 1 & 2 & -1 \\ 1 & -1 & 3 & -2 \end{array}\right|$$

## Related questions

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Calculate the determinant $$\left|\begin{array}{rrrr} 4 & 2 & 3 & 4 \\ 1 & 0 & 1 & 2 \\ 1 & -1 & 1 & 0 \\ 5 & 1 & 4 & 3 \end{array}\right|$$
0 answers 195 views
Calculate the determinant $$\left|\begin{array}{rrrr} 4 & 2 & 3 & 4 \\ 1 & 0 & 1 & 2 \\ 1 & -1 & 1 & 0 \\ 5 & 1 & 4 & 3 \end{array}\right|$$Calculate the determinant $$\left|\begin{array}{rrrr} 4 &amp; 2 &amp; 3 &amp; 4 \\ 1 &amp; 0 &amp; 1 &amp; 2 \\ 1 &amp; -1 &amp; 1 &amp; 0 \\ 5 &amp; ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Suppose we have the square matrıx$$ C=\left[\begin{array}{ccc} 1 & 1 & -1 \\ 3 & 0 & -1 \\ -1 & -1 & 2 \end{array}\right] $$0 answers 215 views Suppose we have the square matrıx$$ C=\left[\begin{array}{ccc} 1 & 1 & -1 \\ 3 & 0 & -1 \\ -1 & -1 & 2 \end{array}\right] $$Suppose we have the square matrıx$$ C=\left\begin{array}{ccc} 1 &amp; 1 &amp; -1 \\ 3 &amp; 0 &amp; -1 \\ -1 &amp; -1 &amp; 2 \end{array}\right $$... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Suppose $A=\left[\begin{array}{cc}0 & -2 \\ 3 & 1 \\ -1 & 4\end{array}\right]$ and $B=\left[\begin{array}{cc}3 & 1 \\ 2 & -2 \\ 0 & -2\end{array}\right]$ 1 answer 295 views Suppose $A=\left[\begin{array}{cc}0 & -2 \\ 3 & 1 \\ -1 & 4\end{array}\right]$ and $B=\left[\begin{array}{cc}3 & 1 \\ 2 & -2 \\ 0 & -2\end{array}\right]$Suppose $A=\left\begin{array}{cc}0 &amp; -2 \\ 3 &amp; 1 \\ -1 &amp; 4\end{array}\right$ and $B=\left\begin{array}{cc}3 &amp; 1 \\ 2 &amp; -2 \\ ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Suppose \(A=\left[\begin{array}{cc}0 & -2 \\ 3 & 1 \\ -1 & 4\end{array}\right]$ and $B=\left[\begin{array}{cc}3 & 1 \\ 2 & -2 \\ 0 & -2\end{array}\right]$ 1 answer 303 views Suppose $A=\left[\begin{array}{cc}0 & -2 \\ 3 & 1 \\ -1 & 4\end{array}\right]$ and $B=\left[\begin{array}{cc}3 & 1 \\ 2 & -2 \\ 0 & -2\end{array}\right]$Suppose $A=\left\begin{array}{cc}0 &amp; -2 \\ 3 &amp; 1 \\ -1 &amp; 4\end{array}\right$ and $B=\left\begin{array}{cc}3 &amp; 1 \\ 2 &amp; -2 \\ ... close 0 answers 230 views Solve the system \left\{\begin{array}{l} 4 x_{1}+2 x_{2}+3 x_{3}+4 x_{4}=0 \\ x_{1}+x_{3}+2 x_{4}=1 \\ x_{1}-x_{2}+x_{3}=1 \\ -3 x_{1}-2 x_{2}-2 x_{3}-2 x_{4}=1 \end{array}\right. Solve the system \left\{\begin{array}{l} 4 x_{1}+2 x_{2}+3 x_{3}+4 x_{4}=0 \\ x_{1}+x_{3}+2 x_{4}=1 \\ x_{1}-x_{2}+x_{3}=1 \\ -3 x_{1}-2 x_{2}-2 x_ ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Suppose \(A=\left[\begin{array}{ccc}0 & 5 & -1 \\ 2 & 1 & 4\end{array}\right]$ and $B=\left[\begin{array}{cc}4 & -1 \\ 2 & 10\end{array}\right]$ 1 answer 332 views Suppose $A=\left[\begin{array}{ccc}0 & 5 & -1 \\ 2 & 1 & 4\end{array}\right]$ and $B=\left[\begin{array}{cc}4 & -1 \\ 2 & 10\end{array}\right]$Suppose $A=\left\begin{array}{ccc}0 &amp; 5 &amp; -1 \\ 2 &amp; 1 &amp; 4\end{array}\right$ and $B=\left\begin{array}{cc}4 &amp; -1 \\ 2 &amp; 1 ... close 1 answer 212 views Using the variables \(x, y$ and $z$, write the solution corresponding to the augmented matrix $\left[\begin{array}{ccc|c} 1 & 0 & 0 & 4 \\ 0 & 1 & 0 & 2 \\ 0 & 0 & 1 & -1 \end{array}\right]$Using the variables $x, y$ and $z$, write the solution corresponding to the augmented matrix \ \left\begin{array}{ccc|c} 1 &amp; 0 &amp; 0 &amp; ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Consider the homogeneous linear system $A x=0$ where $A=\left(\begin{array}{rrrr} 1 & 3 & 0 & 1 \\ 1 & 3 & -2 & -2 \\ 0 & 0 & 2 & 3 \end{array}\right) \text {. }$ 0 answers 146 views Consider the homogeneous linear system $A x=0$ where $A=\left(\begin{array}{rrrr} 1 & 3 & 0 & 1 \\ 1 & 3 & -2 & -2 \\ 0 & 0 & 2 & 3 \end{array}\right) \text {. }$Consider the homogeneous linear system $A x=0$ where \ A=\left(\begin{array}{rrrr} 1 &amp; 3 &amp; 0 &amp; 1 \\ 1 &amp; 3 &amp; -2 &amp; -2 \\ 0 &a ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Suppose you are given the matrix $A=\left[\begin{array}{cc} 1 & -2 \\ 3 & 0 \\ -1 & 5 \end{array}\right]$ 1 answer 317 views Suppose you are given the matrix $A=\left[\begin{array}{cc} 1 & -2 \\ 3 & 0 \\ -1 & 5 \end{array}\right]$Suppose you are given the matrix \ A=\left\begin{array}{cc} 1 &amp; -2 \\ 3 &amp; 0 \\ -1 &amp; 5 \end{array}\right \ a. Find the size of the matr ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Find the inverse of the matrix$$ A=\left(\begin{array}{rrr} 2 & 0 & 4 \\ 1 & 2 & 7 \\ 6 & 4 & 22 \end{array}\right) $$0 answers 293 views Find the inverse of the matrix$$ A=\left(\begin{array}{rrr} 2 & 0 & 4 \\ 1 & 2 & 7 \\ 6 & 4 & 22 \end{array}\right) $$Find the inverse of the matrix$$ A=\left(\begin{array}{rrr} 2 &amp; 0 &amp; 4 \\ 1 &amp; 2 &amp; 7 \\ 6 &amp; 4 &amp; 22 \end{array}\right)  ...
close
1 answer 268 views
Using the variables $x, y$ and $z$, write the solution corresponding to the augmented matrix $\left[\begin{array}{ccc|c} 1 & 0 & 0 & -1 \\ 0 & 1 & 0 & 5 \\ 0 & 0 & 1 & 2 \end{array}\right]$Using the variables $x, y$ and $z$, write the solution corresponding to the augmented matrix \ \left\begin{array}{ccc|c} 1 &amp; 0 &amp; 0 &amp; ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Suppose $A=\left[\begin{array}{cc}1 & 3 \\ -1 & 2\end{array}\right]$ and $B=\left[\begin{array}{c}10 \\ 5\end{array}\right]$.
1 answer 291 views
Suppose $A=\left[\begin{array}{cc}1 & 3 \\ -1 & 2\end{array}\right]$ and $B=\left[\begin{array}{c}10 \\ 5\end{array}\right]$.Suppose $A=\left\begin{array}{cc}1 &amp; 3 \\ -1 &amp; 2\end{array}\right$ and $B=\left\begin{array}{c}10 \\ 5\end{array}\right$. a. Find $A ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Consıder the followng system of equations  \left\{\begin{array}{r} x_{1}-3 x_{2}=2 \\ 2 x_{2}=6 \end{array}\right.  0 answers 228 views Consıder the followng system of equations  \left\{\begin{array}{r} x_{1}-3 x_{2}=2 \\ 2 x_{2}=6 \end{array}\right. (a) Consıder the followng system of equations  \left\{\begin{array}{r} x_{1}-3 x_{2}=2 \\ 2 x_{2}=6 \end{array}\right.  (i) write down the coeffic ... close 0 answers 231 views close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 For the matrix $A=\left[\begin{array}{ccc} 1 & 0 & -3 \\ 2 & 3 & 4 \end{array}\right]$ Compute \(3 A$.
1 answer 245 views
For the matrix $A=\left[\begin{array}{ccc} 1 & 0 & -3 \\ 2 & 3 & 4 \end{array}\right]$ Compute $3 A$.For the matrix \ A=\left\begin{array}{ccc} 1 &amp; 0 &amp; -3 \\ 2 &amp; 3 &amp; 4 \end{array}\right \ Compute $3 A$. ...
close